2022
DOI: 10.1101/2022.11.22.517490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Non-invasive Brain Stimulation on Vision: A Systematic Review and Meta-analysis

Abstract: Objective: Multiple studies have explored the use of non-invasive brain stimulation (NIBS) to enhance visual function. These studies vary in sample size, outcome measures, and NIBS methodology. We conducted a systematic review and meta-analyses to assess the effects of NIBS on visual functions in human participants with normal vision. Methods: We followed the PRISMA guidelines, and a review protocol was registered with PROSPERO before study commencement (CRD42021255882). We searched Embase, Medline, PsychInfo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(161 reference statements)
1
0
0
Order By: Relevance
“…This study found that acupuncture at the right Taiyang acupoint of myopic patients increased CS at all spatial frequencies; this is different from the results of the above research. It may be due to the different mechanisms of acupuncture and the tDCS (Zhuang et al, 2013;Bello et al, 2023). In addition, research has found that the acupuncture at the anterior parts of the head can improve CS, which is consistent with the results of this study (Bittner et al, 2014;Blechschmidt et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This study found that acupuncture at the right Taiyang acupoint of myopic patients increased CS at all spatial frequencies; this is different from the results of the above research. It may be due to the different mechanisms of acupuncture and the tDCS (Zhuang et al, 2013;Bello et al, 2023). In addition, research has found that the acupuncture at the anterior parts of the head can improve CS, which is consistent with the results of this study (Bittner et al, 2014;Blechschmidt et al, 2017).…”
Section: Discussionsupporting
confidence: 88%